MODERN TENDENCIES IN MEDIA DISCOURSE - Tavadze, Lali; Diasamidze, Ivdit; Katamadze, Natia; Davitadze, Lia (International Journal of Innovative Technologies in Social Science, 2024)
What is media discourse? Media discourse refers to interactions that take place through a broadcast platform, whether spoken or written, in which the discourse is oriented to a non-present reader, listener or viewer. Key examples of discourse analysis include the study of television, film, newspaper, advertising, political speeches, and interviews. Modern media comes in many different formats, including print media (books, magazines, newspapers), television, movies, video games, music, cell phones, various kinds of software, and the Internet. Each type of media involves both content and also a device or object through which that content is delivered. Discourse itself may be understood in a few different ways. For one, it may simply refer to the manner in which individuals and groups communicate. On a deeper level, though, it can symbolize the systems of thoughts and beliefs that determine how individuals understand and interpret the world. Mediadriven discourse in the first sense would include the various outlets that individuals in the media use, such as newspapers and magazines, television, radio, and the Internet. If discourse is understood as the beliefs that guide media output, then principles like objectivity or ideological bias might describe it best. One of the most powerful semantic notions in a critical news analysis is that of implication. Words, clauses, and other textual expressions may imply concepts or propositions which may be inferred on the basis of background knowledge. The idea of something hidden is very attractive for the reader. It is worth noting that the world of press and media is involving and eye-catching. One of the widely used techniques in the newspaper universe is that of creating appealing, interesting, alluring and unusual headlines thus involving the readers and building the infinite world of press and media.